Nucleus accumbens functional connectivity changes underlying alcohol expectancies in bipolar disorder and prospective alcohol outcomes: a within-subject randomized placebo-controlled alcohol administration fMRI study - Lippard, Elizabeth T. C.; Kirsch, Dylan E.; Le, Vanessa; Lee, Skyler; Bibb, Nadia; Meek, Kaitlyn; Kosted, Raquel; Huffman, Ansley; Almeida, J. R. C.; Fromme, Kim; Strakowski, Stephen M. (Frontiers in Neuroscience, 2025)
IntroductionAlcohol use disorder (AUD) occurs at higher rates in individuals with bipolar disorder compared to the general population. A paucity of data are available on specific mechanisms that may contribute to bipolar and AUD co-occurrence. We recently reported differences in alcohol expectancies and placebo response during alcohol administration in early-stage bipolar disorder, compared to healthy young adults. This current report investigated subjective and neural response following placebo beverage consumption in young adults with bipolar disorder.MethodsAs part of a within-subject placebo-controlled alcohol administration study, 54 young adults (53% with bipolar disorder type I, agemean + SD = 23 + 2 years, 64% female) completed resting state functional MRI (rsfMRI) scans at baseline (pre-beverage) and following placebo and alcohol consumption (counter-balanced). Participants completed subjective response measures during placebo and alcohol beverage conditions. Between-group differences in subjective response and placebo-related changes in functional connectivity of the Nucleus Accumbens (NAc) with other brain regions, compared to a pre-beverage rsfMRI baseline condition, were investigated. Fisher-transformed correlation coefficients between ROIs and seed-to-clusters showing a significant group-by-condition (placebo, pre-beverage rsfMRI) interaction were calculated. Associations with prospective alcohol use and problems were explored in a subgroup with longitudinal data.ResultsYoung adults with bipolar disorder reported greater intoxication during the placebo condition, compared to healthy young adults (main effects of group: p < 0.05). Compared to pre-beverage rsfMRI, the placebo condition related to increased connectivity between bilateral NAc and regions within the sensorimotor network in bipolar disorder. Comparison participants showed the opposite pattern of placebo-related changes in connectivity (group-by-condition, p-FDR < 0.05). Greater anxiolytic effects endorsed during placebo and associated increases in NAc functional connectivity related to greater alcohol use and alcohol problems at follow-up in bipolar disorder (p < 0.05).DiscussionResults suggest differences in placebo response in bipolar disorder, including distinct neural correlates, that may relate to prospective alcohol use/problems. Given the theoretical association between placebo response and self-reported alcohol expectancies, findings could open the door to interventions aimed at changing expectancies.